Involvement of Oxidative Stress in Resistance to Tyrosine-Kinase Inhibitors Therapy in Chronic Myeloid Leukemia - PASCU (VÎNTURIŞ), EMILIA GEORGIANA (Curr Health Sci J, 2020)
Oxidative stress involves disruption of the cellular redox status through excessive production of reactive oxygen species or through deficiency in the cellular antioxidant capacity. It is involved in the pathogeny of multiple entities (hematological diseases, metabolic disorders, cardiovascular and renal pathology etc.), as well as in the pharmacokinetics of specific treatments for these pathologies. Chronic myeloid leukemia is a chronic myeloproliferative disease for which current standard treatment is BCR-ABL tyrosine kinase inhibitors. The innovation of this therapy has significantly improved life expectancy for patients with chronic myeloid leukemia, but in some cases, this treatment becomes ineffective, installing the resistance to tyrosine kinase inhibitors therapy. There were described two types of tyrosin kinase inhibitors resistance: primary and secondary resistance. In the present paper we proposed to evaluate the involvement of oxidative in the resistance to tyrosine kinase inhibitors therapy, in the clonal instability in chronic myeloid leukemia and in the progression of the disease to an advanced stage. We concluded that oxidative stress can play a dual role in the evolution of chronic myeloid leukemia: on the one hand it can promote genomic instability and accelerate the progression of the disease to advanced stages associated with tyrosin kinase inhibitors resistance and, on the other hand, it can contribute to leukemic cell apoptosis. It seems to be outlined a fragile balance between the pro- and anti-apoptotic effects of the reactive oxygen species, closely related to their level in the leukemic cells.